Community Participation in the Expansion Planning of Majonofmigi Village in the Mayamuk District, Sorong Regency - Rusdi; Muhammad Ali; Deflan Partada; Ismed Kelibay (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the extent of community participation in planning the expansion of Majonofmigi Village with the government to divide Majonofmigi Village into a definitive village so that all management of Majonofmigi Village no longer depends on Yeflio's parent village. the fields of Development (devlotment), Social Culture, Economics, and Politics. What is also expected by the government in this case is to accelerate the division of villages so that in the future there will be collaboration between the Sorong Regency Government, the Province and the central government to be more synergistic for a prosperous and prosperous Indonesia